Scabies: Clinical Pearls for Community Dermatologists (Canadian Dermatology Today, 2025)
Scabies is a common parasitic skin infestation caused by Sarcoptes scabiei var. hominis, with an estimated global burden of over 200 million cases annually. Scabies remains underdiagnosed and can often be challenging to manage. Institutional outbreaks, diagnostic delays, and treatment failures contribute to ongoing morbidity. This practical literature review summarizes clinical pearls for community dermatologists, integrating recent diagnostic frameworks, treatment evidence, and evolving considerations related to drug resistance and public health control.